2019
DOI: 10.3389/fimmu.2019.00097
|View full text |Cite
|
Sign up to set email alerts
|

New Insights for RANKL as a Proinflammatory Modulator in Modeled Inflammatory Arthritis

Abstract: Receptor activator of nuclear factor-κB ligand (RANKL), a member of the Tumor Necrosis Factor (TNF) superfamily, constitutes the master regulator of osteoclast formation and bone resorption, whereas its involvement in inflammatory diseases remains unclear. Here, we used the human TNF transgenic mouse model of erosive inflammatory arthritis to determine if the progression of inflammation is affected by either genetic inactivation or overexpression of RANKL in transgenic mouse models. TNF-mediated inflammatory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…ratio observed in cells with OGM, as compared with cells incubated with PRPEs, can be explained by both a time-dependent increase of RANKL expression, induced by different cell maturation stages (82) and by the anti-inflammatory action of polyphenols (83)(84)(85)(86), which determined the RANKL downregulation in cells treated with both PRPEs. Notwithstanding the evidence that RANKL is a member of the tumor necrosis factor family, which is not only involved in osteoclastogenesis but also in the regulation of the immune system (87), the absence of data on direct inflammation is a limitation of this study and needs to be further investigated. This is of particular importance because osteoclastogenesis requires the signaling involving the mediator of the inflammatory response nuclear factor-κB, activated by RANKL cytokine, to occur (88).…”
Section: Discussionmentioning
confidence: 99%
“…ratio observed in cells with OGM, as compared with cells incubated with PRPEs, can be explained by both a time-dependent increase of RANKL expression, induced by different cell maturation stages (82) and by the anti-inflammatory action of polyphenols (83)(84)(85)(86), which determined the RANKL downregulation in cells treated with both PRPEs. Notwithstanding the evidence that RANKL is a member of the tumor necrosis factor family, which is not only involved in osteoclastogenesis but also in the regulation of the immune system (87), the absence of data on direct inflammation is a limitation of this study and needs to be further investigated. This is of particular importance because osteoclastogenesis requires the signaling involving the mediator of the inflammatory response nuclear factor-κB, activated by RANKL cytokine, to occur (88).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis warrants further investigation but would be in line with the high levels of free RANKL in human SLE and RA patients ( Carmona-Fernandes et al, 2011 ; Fonseca et al, 2005 ). Moreover, a recent study using murine RA models reported progressively increased RANKL levels in the diseased mice, which positively correlated with disease severity ( Papadaki et al, 2019 ). While the genetic inactivation of RANKL dramatically attenuated arthritis, the overexpression of RANKL exacerbated RA in these animals ( Papadaki et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, several proteins, such as MMP-9, E-Cadherin, Syncytin-1, CD200, dendrocyte expressed seven transmembrane protein (DC-STAMP), osteoclast stimulatory transmembrane protein (OC-STAMP), CD44, and P2X7, have been identified that play a role in macrophage fusion (for review see: [34,35,57]). It is also known that the expression of these proteins is induced by cytokines, such as IL-4 and RANKL [67][68][69][70][71], suggesting that these factors are likely involved in the transition of macrophages from a non-fusogenic to a pro-fusogenic state. Nonetheless, the detailed process of macrophage fusion remains unclear.…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 99%
“…In this context, it has been shown that the pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) might also be a mediator of cell fusion. Osteoclastogenesis [70,74,75], as well as the fusion of cancer cells with endothelial cells [63,76], mesenchymal stem cells [64], or breast epithelial cells [72,73,77] can be induced by TNF-α. Some data revealed that TNF-α could mediate fusion due to induction of MMP-9 expression [73,75], which plays a role in osteoclastogenesis and giant cell formation [75,78].…”
Section: How Do Cells Fuse With Each Other?mentioning
confidence: 99%